Islamic Spiritual Leadership Model to Enhance Madrasah Quality Culture and Achieve Sustainable Development Goals - Mahmud, Muchammad Eka; Ramli, Akhmad (Al-Hayat: Journal of Islamic Education, 2025)
This study emphasises the importance of spiritual leadership as a key strategy in supporting the achievement of SDG 4 (Quality Education) and SDG 16 (Resilient Institutions), considering that leadership practices in State Islamic Senior High Schools (MAN) in Java and Kalimantan are still diverse and lack cross-cultural comparative studies. The research objective is to analyse spiritual leadership practices, identify similarities and differences across regions, assess their contribution to a quality culture, and formulate a conceptual model of spiritual leadership based on Islamic values appropriate to the educational context and the SDGs agenda. This research uses a qualitative approach with an interpretative paradigm through a multi-site study in six MANs, with informants from madrasah principals, teachers, and students selected through purposive and snowball sampling. The results show that spiritual leadership is the primary foundation of a quality culture through exemplary behaviour, habituation of worship, strengthening of the vision and mission, and empowerment of teachers and students. Practices in Java are more formal-strategic, while in Kalimantan they tend to be contextual-collective, based on religiosity and local wisdom, despite facing budget constraints, administrative pressures, and socio-cultural diversity. This study developed an Islamic Spiritual Leadership model for the SDGs based on faith, Islam, ihsan, Al-Ghazali's values, and the principles of the caliphate ('adl, rahma, amanah), formulated in four pillars: spiritual transcendence, ethical role model, community empowerment, and contextual adaptation. The study's limitations lie in its regional scope and the predominance of qualitative data. Further research is recommended to use a quantitative or mixed-methods approach to test the model's effectiveness more broadly. The study's primary contribution is presenting a contextual and applicable Islamic perspective in strengthening the quality culture of madrasas while supporting the global agenda of sustainable development.